2019
DOI: 10.1111/ctr.13772
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing transfusion‐associated HLA sensitization in patients bridged to heart transplantation using ventricular assist device

Abstract: Background:Bridging heart failure patients with mechanical ventricular assist devices (VAD) enables access to transplantation. However, VAD is associated with increased risk for anti-HLA antibodies associated with rejection of subsequent allografts.Factors determining alloantibody formation in these patients remain undefined. Methods:We performed a single-center retrospective cohort study of 164 patients undergoing heart transplantation from 2014 to 2017. Medical records including use of VAD, transfused blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Single center studies have demonstrated that de novo HLA sensitization on LVAD support is associated with longer times to transplantation as well as increased risk of acute cellular and humoral rejection in the posttransplant period. 5,14,15 A recent analysis of the UNOS registry suggested pretransplant allosensitization (PRA > 10%) was not associated with increased 5-year posttransplant mortality in patients bridged with MCS devices, but it is difficult to draw conclusions from this study as it remains unclear whether allosensitization occurred after implantation of LVAD or if patients were already sensitized before device implant. 16 Aside from HLA sensitization, LVAD implantation is associated with development of polyreactive natural IgG antibodies (Nabs) which are associated with primary graft dysfunction but not rejection.…”
Section: Discussionmentioning
confidence: 86%
“…Single center studies have demonstrated that de novo HLA sensitization on LVAD support is associated with longer times to transplantation as well as increased risk of acute cellular and humoral rejection in the posttransplant period. 5,14,15 A recent analysis of the UNOS registry suggested pretransplant allosensitization (PRA > 10%) was not associated with increased 5-year posttransplant mortality in patients bridged with MCS devices, but it is difficult to draw conclusions from this study as it remains unclear whether allosensitization occurred after implantation of LVAD or if patients were already sensitized before device implant. 16 Aside from HLA sensitization, LVAD implantation is associated with development of polyreactive natural IgG antibodies (Nabs) which are associated with primary graft dysfunction but not rejection.…”
Section: Discussionmentioning
confidence: 86%
“…It is not known if patients with low/moderate levels (MFI < 10 000) of pre‐transplant DSA have acceptable post‐transplant outcomes. Currently, the number of sensitized patients awaiting heart transplantation has been increasing, primarily due to blood transfusions, pregnancies, prior organ transplantations, and increasing implantation of mechanical circulatory support devices 5,6 . Patients implanted with ventricular‐assist devices (VAD) as a bridge to transplant especially carry a significant risk of sensitization and possibly a higher risk of post‐transplant antibody‐mediated rejection (AMR), allograft failure, and mortality 6 …”
Section: Introductionmentioning
confidence: 99%
“…Even so, the blood transfusion required to treat anemia in patients with CKD continues to be widely used, especially in patients with inflammation status who progress to kidney failure with replacement therapy requirements [13,14]. Moreover, red blood cell (RBC) transfusion presents risks and complications, such as infections and increased sensitization to HLA antigens for kidney transplantation [15,16].…”
Section: Introductionmentioning
confidence: 99%